External validation of the albumin, C-reactive protein and lactate dehydrogenase model in patients with metastatic renal cell carcinoma receiving second-line axitinib therapy in a Japanese multi-center cohort. (22nd January 2021) - Tamura, Keita; Osawa, Takahiro; Takeuchi, Ario; Minami, Keita; Nakai, Yasutomo; Ueda, Kosuke; Ozawa, Michinobu; Uemura, Motohide; Sugimoto, Mikio; Ohba, Kojiro; Suzuki, Toshihiro; Anai, Satoshi; et al.
Abstract: Purpose: To externally validate the utility of the albumin, C-reactive protein and lactate dehydrogenase model to predict the overall survival of previously treated metastatic renal cell carcinoma patients. Patients and methods: The ability of the albumin, C-reactive protein and lactate dehydrogenase model to predict overall survival was validated and compared with those of other prognostication models using data from 421 metastatic renal cell carcinoma patients receiving second-line axitinib therapy at 36 hospitals belonging to the Japan Urologic Oncology Group. Results: The following factors in this cohort were independently associated with poor overall survival in a multivariate analysis: a low Karnofsky performance status, <1 year from diagnosis to targeted therapy, a high neutrophil count, and low albumin, elevated C-reactive protein, and elevated lactate dehydrogenase, and the Japan Urologic Oncology Group model was newly developed based on the presence/absence of these independent factors. In this cohort, 151 (35.9%), 125 (27.7%) and 145 (34.4%) patients were classified into the favorable, intermediate and poor risk groups, respectively, according to the albumin, C-reactive protein and lactate dehydrogenase model; however, the proportions of patients in the intermediate risk group stratified by the Japan Urologic Oncology Group, Memorial Sloan Kettering Cancer Center and International Metastatic Renal Cell Carcinoma Database Consortium models were >50%. The superiority of the albumin, C-reactive protein and lactate dehydrogenase model to the Memorial Sloan Kettering Cancer Center and International Metastatic Renal Cell Carcinoma Database Consortium models, but not the Japan Urologic Oncology Group model, was demonstrated by multiple statistical analyses. Conclusions: The utility of the albumin, C-reactive protein and lactate dehydrogenase model as a simple and objective prognostication tool was successfully validated using data from 421 metastatic renal cell carcinoma patients receiving second-line axitinib. Abstract : The albumin, C-reactive protein and lactate dehydrogenase model to predict overall survival was externally validated for metastatic renal cell carcinoma patients receiving second-line axitinib therapy and had better performance compared with the Memorial Sloan Kettering Cancer Center and International Metastatic Renal Cell Carcinoma Database Consortium models.